Genetic Relationships between Iranian and Armenian Darevskia raddei Lizards (Journal of Innovative Solutions for Eco-Environmental Sustainability, 2025)
Darevskia raddei sensu lato is a complex species of Caucasian rock lizards. It consists of four subspecies: D. r. raddei, D. r. nairensis, D. r. vanensis and D. r. chaldoranensis, whose phylogenetic status and relationships are still under discussion. Furthermore, D. raddei is the maternal parent of five parthenogenetic species originating through reticular speciation. In the present work, we used microsatellite markers to study D. raddei populations from Iran and their phylogenetic relationships with Armenian and Artsakh (Nagorno-Karabakh) populations. Previously, we demonstrated a deep divergence of the D. raddei complex inhabiting this territory, not only into the subspecies D. r. nairensis and D. r. raddei, but also between groups of populations that we named D. r. raddei TT and D. r. raddei GG. We characterized D. raddei samples from six localities in Iran: five representing D. r. raddei and one D. r. chaldoranensis. Significant genetic similarity was shown between Iranian populations of D. r. raddei and the subspecies of D. r. chaldoranensis. This analysis suggests that Iranian populations are more closely aligned with the D. r. raddei GG group (includes populations from Geghard, Goris, Yeghegnadzor, and Kajaran in Armenia). Lizards from this group are typically smaller and are distinguished by their less green and more pronounced yellow ventral coloration and a subdued dorsal pattern. Therefore, this study provides the first molecular genetic characterization of D. raddei lizards from Iran and their proximity with D. raddei populations from southern Armenia. This research was supported by Russian Science Foundation Grant No. 25-14-00028.
Keywords: genetic polymorphism; genetic divergence; microsatellite loci; Darevskia raddei